2017
DOI: 10.1038/s41598-017-10835-8
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis contributes to chronic constipation development via regulation of serotonin transporter in the intestine

Abstract: Chronic constipation is a prevalent functional gastrointestinal disorder accompanied with intestinal dysbiosis. However, causal relationship between dysbiosis and constipation remains poorly understood. Serotonin transporter (SERT) is a transmembrane transport protein which re-uptakes excessive 5-hydroxytryptamine (5-HT) from effective location to terminate its physiological effects and involves in regulating gastrointestinal motility. In this study, fecal microbiota from patients with constipation and healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
155
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(164 citation statements)
references
References 66 publications
3
155
0
6
Order By: Relevance
“…Asian Americans have higher rates of type 2 diabetes and pathogenic infections than Caucasians (66), and two metagenomic functions enriched in control versus type 2 diabetes cases appear to be largely conferred by cluster-associated butyrate-producing and motility-inducing Verrucomicrobiaceae and Clostridia taxa reduced in abundance among AGP and HMP Asian-Pacific Islanders (11). Both induction of cell motility and butyrate promotion of mucin integrity can protect against pathogenic colonization and associate with microbial community changes (11, 58, 67). Levels of cell motility and butyrate are key factors suspected to underlie a range of health disparities including inflammatory bowel disease, arthritis, and type 2 diabetes (11, 68–70).…”
Section: Discussionmentioning
confidence: 99%
“…Asian Americans have higher rates of type 2 diabetes and pathogenic infections than Caucasians (66), and two metagenomic functions enriched in control versus type 2 diabetes cases appear to be largely conferred by cluster-associated butyrate-producing and motility-inducing Verrucomicrobiaceae and Clostridia taxa reduced in abundance among AGP and HMP Asian-Pacific Islanders (11). Both induction of cell motility and butyrate promotion of mucin integrity can protect against pathogenic colonization and associate with microbial community changes (11, 58, 67). Levels of cell motility and butyrate are key factors suspected to underlie a range of health disparities including inflammatory bowel disease, arthritis, and type 2 diabetes (11, 68–70).…”
Section: Discussionmentioning
confidence: 99%
“…However, as the balance can be disrupted by various factors including host genetics, diet, antibiotics and stress, altered microorganisms potentially initiate and perpetuate different disorders. 5 Various studies have shown that microbial alternations, characterized by a marked increase in the numbers of pathogens and a relative decrease in levels of beneficial bacteria, are connected with the development of gastrointestinal and extra-gastrointestinal cancers. [6][7][8][9][10][11][12][13] Altering the gut microbiota is expected as a novel method to deal with diseases associated with intestinal dysbiosis.…”
Section: Introductionmentioning
confidence: 99%
“…Genus level analyses further showed decreased relative abundance of Clostridium , Lactobacillus , Desulfovibrio and Methylobacterium and increased relative abundance of Bacteroides and Akkermansia . The findings suggest a potential role for gut microbiota in the pathogenesis of chronic constipation via increased expression of 5-HT transporter 158 . Interestingly, gut microbiota changes resulting from constipation can further impact GI motility, suggesting a more complex interaction with feedforward regulation rather than a simple cause-effect relationship 53 .…”
Section: Functional Gi Disordersmentioning
confidence: 83%
“…Investigation of the causal relationship between alterations in gut microbial communities and constipation has been described in a recent study 158 reporting upregulation of 5-HT transporter and decreased 5-HT content in the colonic tissue of germ-free mice that received fecal microbiota from constipated patients. 5-HT was negatively correlated with transit time and changes were accompanied by decreased relative abundance of the phylum Firmicutes and increased Bacteroidetes in mice receiving fecal microbiota from constipated patients.…”
Section: Functional Gi Disordersmentioning
confidence: 99%